The Effect of Game-Based Learning on Motivation and Learning Strategies of Nursing Students in Occupational Health Nursing Course - Sevcan Topçu (Jurnal Berita Ilmu Keperawatan, 2023)
Aim of this study is to evaluate the effect of game-based learning on the motivation and learning strategies of nursing students. A quasi-experimental research design that was with a pre-post test design without a control group was used in this research. The sample of the study consisted of 74 third grade students. The Sociodemographic Characteristics Question Form and Motivated Strategies for Learning Questionnaire were used for data collection tool. The mean age of nursing students is 21.45±0.62. 85.1% of them are women. A statistically significant difference was found between the pre- and the post-test mean of the nursing students' subscales of control of learning beliefs, intrinsic goal orientation, test anxiety, self-efficacy for learning and performance (p<0.05). There were statistically significant differences between the pre and post-test Learning Strategies Scale subscale scores, nursing students obtained higher mean scores from critical thinking, help seeking, peer learning, metacognitive self-regulation subscales at the post-test (p<0.05). As a result of this study, it was found that Kahoot! has an important influence on the motivation and learning strategies of nursing students. In the development of learning in students' theoretical and practical training, using Kahoot! which is one of the game-based student response systems will be useful.